Variability of Droughtiness in The Climatic Spectrum of The South Indian Region - Sarma, A A L N (Annals of Arid Zone, 2016)
The paper is concerned with the decadal droughtiness variation. The aridity index of Thornhwaite (1948) has been used as the central parameter for assessing the droughtiness of a station. Decadal variations in droughtiness were computed and the mean values of it at a station for a climatic type were graphically plotted.